Fluency and communication strategy use in group interactions for occupational purposes - Ting, Su Hie; Megawati, Soekarno (JELTIM, 2020)
Communication strategy use varies with proficiency in the target language and less proficient learners rely on L1 strategies for conversational repair. In an English for Occupational Purposes (EOP) context where the technical register is unfamiliar, little is known on whether communication strategies can enable learners with limited English proficiency to overcome hesitancy in speech. The study examined learners’ use of communication strategies and fluency in group interactions in an EOP context using an integrated problem-solving, interactional and discourse-based framework of communication strategies. A 13-week communication strategy training was conducted focusing on conversational repair strategies (fillers, approximation, code-switching), meaning negotiation strategies (clarification request, comprehension check, confirmation check), response strategies (rephrase, shadowing, reply) and discourse-based strategies (lexical repetition, topic fronting). The results on communication strategy use in three group interaction sessions involving three participants showed that the most frequently used communication strategies were lexical repetition and fillers. The participants’ fluency, as measured in C-units and frequency of fillers, was higher when they interacted on familiar topics. The participants learnt to use discourse-based strategies but not meaning negotiation strategies. The findings suggest that for better negotiation of meaning, the communication strategy training needs to create metacognitive awareness of the interlocutors’ communicative needs.